Mengukur Tingkat Kepuasan Pengguna SIGESIT Kabupaten Bima Menggunakan System Usability Scale Dan Pieces Framework - Valian Yoga Pudya Ardhana (JURIKOM (Jurnal Riset Komputer), 2022)
SIGESIT is an application owned by the local government of Bima Regency which is managed by market managers throughout Bima Regency to provide market information that is accountable, transparent and participatory. This SIGESIT application was created to overcome market management problems that are not in accordance with the prevailing policy directions. So that with the SIGESIT application, market management, totaling 30 markets in Bima Regency can be monitored in real time to uphold the principles of transparency and accountability. However, since the application was launched, the level of user satisfaction has not been tested, in this case the market operator throughout Bima Regency. Therefore, in this study an evaluation was carried out by measuring the level of satisfaction of SIGESIT users using 2 methods, namely the System Usability Scale and the PIECES Framework. The results obtained using the Pieces Framework method is a value of 4.22 which is taken from the average value of 6 domains. This value is in the very satisfied category. While the results of the SIGESIT user satisfaction level based on the System Usability Scale method are obtained a value of 74.01 where the value for the acceptability range version is Acceptable, while the grade scale results from the level of user acceptance are included in class B. Based on the results of measurements using these 2 methods The results obtained are almost the same, which shows that SIGESIT is accepted by users and is suitable for use